Relationship between lipoprotein(a) and colorectal cancer among inpatients: a retrospective study - Wang, Huijie; Zheng, Huanwei; Meng, Ping; Cao, Xu; Liu, Jinli; Zhang, Teng; Zuo, Haiying; Wang, Zhichao (Frontiers in Oncology, 2023)
The present study was to explore the association between lipoprotein(a) [Lp(a)] and colorectal cancer (CRC) among inpatients. This study included 2822 participants (393 cases vs. 2429 controls) between April 2015 and June 2022. Logistic regression models, smooth curve fitting, and sensitivity analyses were performed to investigate the relationship between Lp(a) and CRC. Compared with the lower Lp(a) quantile 1 (<79.6 mg/L), the adjusted odds ratios (ORs) in quantile 2 (79.6-145.0 mg/L), quantile 3 (146.0-299.0 mg/L), and quantile 4 (≥300.0 mg/L) were 1.41 (95% confidence interval [CI]: 0.95–2.09), 1.54 (95% CI: 1.04–2.27), 1.84 (95% CI: 1.25–2.7), respectively. A linear relationship between lipoprotein(a) and CRC was observed. The finding that Lp(a) has a positive association with CRC supports the "common soil" hypothesis of cardiovascular disease (CVD) and CRC.